2015
DOI: 10.1016/j.niox.2014.09.158
|View full text |Cite
|
Sign up to set email alerts
|

Acute whole body UVA irradiation combined with nitrate ingestion enhances time trial performance in trained cyclists

Abstract: Dietary nitrate supplementation has been shown to increase nitric oxide (NO) metabolites, reduce blood pressure (BP) and enhance exercise performance. Acute exposure to ultraviolet (UV)-A light also increases NO bioavailability and reduces BP. We conducted a randomized, counterbalanced placebo-controlled trial to determine the effects of UV-A light alone and in combination with nitrate on the responses to sub-maximal steady-state exercise and time trial (TT) performance. Nine cyclists (VO2max 53.1 ± 4.4 ml/kg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 34 publications
1
36
0
Order By: Relevance
“…With a burgeoning awareness of the potential importance of NO 3 -in sport and exercise, an ever-increasing variety of NO 3 -fortified products are becoming commercialised, ranging from sport bars and lozenges to BR capsules. Importantly, NO 3 -salts (in solution or via capsule) are readily available for both oral and intravenous administration and ] ratio, as defined in Table 1) was relatively consistent (1.0-1.2) and is in keeping with the work of most using BR [11][12][13][14], but inconsistent with Webb et al hrs, and a plasma t½ of >6 hrs is found irrespective of KNO 3 dose (4 -24 mmol).…”
Section: Nitrate (No 3 -) Sourcementioning
confidence: 70%
See 3 more Smart Citations
“…With a burgeoning awareness of the potential importance of NO 3 -in sport and exercise, an ever-increasing variety of NO 3 -fortified products are becoming commercialised, ranging from sport bars and lozenges to BR capsules. Importantly, NO 3 -salts (in solution or via capsule) are readily available for both oral and intravenous administration and ] ratio, as defined in Table 1) was relatively consistent (1.0-1.2) and is in keeping with the work of most using BR [11][12][13][14], but inconsistent with Webb et al hrs, and a plasma t½ of >6 hrs is found irrespective of KNO 3 dose (4 -24 mmol).…”
Section: Nitrate (No 3 -) Sourcementioning
confidence: 70%
“…Certainly in our hands [13] there remains noticeable variation in both time to peak, and peak plasma [ . It is tempting to speculate this reflects mainly differences in dealing with and/or storing the plasma sample as we and others have demonstrated [15].…”
Section: Individual Versus Group Variationmentioning
confidence: 96%
See 2 more Smart Citations
“…Despite these apparent acute benefits to supramaximal exercise resulting from dietary nitrate shown that NO metabolites appear to reach peak concentrations in the plasma faster when 258 ingesting the nitrate gels compared to beetroot juice (1-1.5 h and 2.5-3 h, respectively) 23 . It 259 remains to be determined whether these pharmacokinetic dissimilarities are due to individual 260 differences or the inherent characteristics of the supplements themselves.…”
mentioning
confidence: 99%